2018
DOI: 10.1371/journal.pone.0202748
|View full text |Cite
|
Sign up to set email alerts
|

Manchette-acrosome disorders and testicular efficiency decline observed in hypercholesterolemic rabbits are recovered with olive oil enriched diet

Abstract: High-fat diet is associated with hypercholesterolemia and seminal alterations in White New Zealand rabbits. We have previously reported disorders in the development of the manchette-acrosome complex during spermiogenesis and decreased testicular efficiency in hypercholesterolemic rabbits. On the other hand, olive oil incorporated into the diet improves cholesterolemia and semen parameters affected in hypercholesterolemic rabbits. In this paper, we report the recovery—with the addition of olive oil to diet—from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 41 publications
(70 reference statements)
1
9
0
Order By: Relevance
“…By using either olive oil (as a source of monounsaturated fatty acids (MUFA)) or krill oil (for n -3 PUFA), they showed that olive oil partially neutralized the negative effects of a high-fat diet on sperm quality, increasing gamete mobility, reducing oxidative stress (lipoperoxidation), and slightly improving mitochondria function [55]. These data are in accordance with beneficial effects of olive oil demonstrated on spermatozoa from hypercholesterolemic rabbits, as described above [17, 19]. In mice, data on dietary lipid supplementation and its effect on sperm function are rare.…”
Section: Lipid Overload and Oxidative Stress: Links Consequencessupporting
confidence: 66%
See 1 more Smart Citation
“…By using either olive oil (as a source of monounsaturated fatty acids (MUFA)) or krill oil (for n -3 PUFA), they showed that olive oil partially neutralized the negative effects of a high-fat diet on sperm quality, increasing gamete mobility, reducing oxidative stress (lipoperoxidation), and slightly improving mitochondria function [55]. These data are in accordance with beneficial effects of olive oil demonstrated on spermatozoa from hypercholesterolemic rabbits, as described above [17, 19]. In mice, data on dietary lipid supplementation and its effect on sperm function are rare.…”
Section: Lipid Overload and Oxidative Stress: Links Consequencessupporting
confidence: 66%
“…These defects were shown to be due to an abnormal interaction between the manchette-acrosome complex and the membrane microdomains. Here, the authors demonstrated that a dietary intake of 7% olive oil combined with HCD could restore a normal phenotype [19]. Unfortunately, the authors did not propose any hypothesis on how olive oil dietary supplementation could act to restore a normal phenotype.…”
Section: Dietary Cholesterol and Male Infertilitymentioning
confidence: 99%
“…An observational study demonstrated that underweight and overweight individuals have a lower semen quality, in terms of total sperm number and total motile sperm count ( 33 ). Adverse effects of a high fat ( 34 ) or high cholesterol intake ( 35 ) on the structure and function of the testes have been reported. In this study, HFC consumption induced pathological damage in testicular tissue and impaired spermatogenesis in terms of reduction of the germinal epithelium thickness, fewer mature spermatozoa, and a poor semen quality.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we informed that hypercholesterolemic rabbits showed sperm head defects under a HFD [3, 4]. These spermatogenic defects were prevented by reducing dietary fat and supplementing with olive oil [4, 29]. This and other evidences [1, 13, 30] suggest that systemic oxidative stress and inflammation may play a key role in the accumulation of cholesterol in the testicles, as well as cytoskeleton disorganization during spermiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…An abnormal head shape can be caused by an anomalous shape of the nucleus due to the ectopic position of the manchette's microtubules [39]. This probably causes an alteration in the anchorage of the microtubules (as seen in rabbits), which probably results in the abnormal shape of the sperm heads [4, 29].…”
Section: Discussionmentioning
confidence: 99%